Relationship between Body Mass Index with Menstrual Cycle in Senior High School Students - Rinasyah Ganesh; Lola Ilona; Ryadi Fadil (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: In recent years, there is an escalation of menstrual disorders in both developing and developed countries. One of the important factors that contribute to menstrual disorders is body fat content. In developing countries like Indonesia, young women in certain cultures get married at average age of 16 years. At the same time, the number of malnourishment among adolescent is increasing. This study was conducted to analyze the relationship between body mass index (BMI) and menstrual cycle in senior high school students.Methods: This study included 330 girls ages 15−17. This study was conducted in Jatinangor, Sumedang from the period of August–October 2013 using a cross-sectional study. Questionnaires assessing their menstruation and their weight and height were collected after obtaining the respondents consent.The collected data were analyzed using the independent T-test.Results: Most of the respondents had normal BMI, menstrual interval, amount and duration. There was no relationship between BMI and menstrual interval and menstrual amount (0.74 and 0.878 respectively), however there was relationship between BMI and menstrual period (p= 0.036).Conclusions: Menstrual abnormalities among female adolescents are common. Based on this study, BMI seems to be moderately associated with menstrual cycle, especially with menstrual period, although a possibility still remains that body fat affects the menstruation superiorly. [AMJ.2015;2(4):555–60] DOI: 10.15850/amj.v2n4.640